2012
DOI: 10.1186/1749-8090-7-70
|View full text |Cite
|
Sign up to set email alerts
|

Primary cardiac B-cell lymphoma with atrioventricular block and paroxysmal ventricular tachycardia

Abstract: Primary cardiac lymphoma (PCL) is very rare, and is extremely challenging to diagnose due to nonspecific symptoms. When discovered, the right atrium and ventricle are most commonly affected, while diffuse cardiac involvement is uncommon. PCL is fatal unless promptly diagnosed and treated. Herein, we present the case of a 36-year-old immunocompetent male who presented with a 5-year history of non-specific chest symptoms and was diagnosed with primary diffuse cardiac large B-cell lymphoma involving the entire he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…As stated by Y. H. Jung et al it is necessary to diagnose PCL as early as possible, to use intensive treatment with new chemotherapy drugs in order to achieve better outcomes for the patients [ 3 ]. K. W. Chen et al and later A. Habertheuer et al reported successful recovery of patients after surgical removal of the tumour and postoperative chemotherapy [ 4 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated by Y. H. Jung et al it is necessary to diagnose PCL as early as possible, to use intensive treatment with new chemotherapy drugs in order to achieve better outcomes for the patients [ 3 ]. K. W. Chen et al and later A. Habertheuer et al reported successful recovery of patients after surgical removal of the tumour and postoperative chemotherapy [ 4 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common histological type of PCL is large B cell lymphoma [ 2 , 3 ]. PCL is fatal, unless it is diagnosed and treated in time [ 4 ]. Patients usually die within few months after being diagnosed with PCL [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCL usually presents after the fifth decade of life and most often involves the right heart chambers [6]. Heart failure and pericardial effusions are the two most commonly reported clinical presentations of PCL [4].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the temporary pacing wire excluded safe use of cardiac Case Reports in Cardiology MRI in this case due to the risk of significant heating or dislodgement. Development of various arrhythmias during chemotherapy has been described and highlights the importance of ongoing arrhythmia surveillance as the tumor substrate changes with treatment [6]. Other reported cases of AV block secondary to PCL with subsequent pacemaker implantation have reported resolution of heart blocks after initiation of chemotherapy without continued pacing requirements [4].…”
Section: Discussionmentioning
confidence: 99%
“…This type of tumor needs to be treated on-time, due to its fatal prognosis. Early diagnosis is mandatory (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%